2015
DOI: 10.3758/s13428-015-0574-3
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic complexity for psychology: a user-friendly implementation of the coding theorem method

Abstract: Kolmogorov-Chaitin complexity has long been believed to be impossible to approximate when it comes to short sequences (e.g. of length 5-50). However, with the newly developed coding theorem method the complexity of strings of length 2-11 can now be numerically estimated. We present the theoretical basis of algorithmic complexity for short strings (ACSS) and describe an R-package providing functions based on ACSS that will cover psychologists' needs and improve upon previous methods in three ways: (1) ACSS is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 93 publications
0
47
0
Order By: Relevance
“…Note that the actual value of the K(S) is uncomputable. b For long strings, it can be approximated by effective string-compression algorithms such as Lempel-Ziv (see Ref 10) implemented in the common utility gzip, 14 meaning that the Kolmogorov complexity of a long string S is approximately the length, in characters, of the gzipped version of S. For shorter strings, such approximations are in principle less reliable, though recent work by Gauvrit et al 15 has for the first time provided practical techniques for estimating the Kolmogorov complexity of short strings, opening an intriguing research avenue for evaluating the role of complexity in psychological models. conveys information given by − log p i , which quantifies the degree of "surprise" or unexpectedness entailed by the message.…”
Section: Kolmogorov Complexitymentioning
confidence: 99%
“…Note that the actual value of the K(S) is uncomputable. b For long strings, it can be approximated by effective string-compression algorithms such as Lempel-Ziv (see Ref 10) implemented in the common utility gzip, 14 meaning that the Kolmogorov complexity of a long string S is approximately the length, in characters, of the gzipped version of S. For shorter strings, such approximations are in principle less reliable, though recent work by Gauvrit et al 15 has for the first time provided practical techniques for estimating the Kolmogorov complexity of short strings, opening an intriguing research avenue for evaluating the role of complexity in psychological models. conveys information given by − log p i , which quantifies the degree of "surprise" or unexpectedness entailed by the message.…”
Section: Kolmogorov Complexitymentioning
confidence: 99%
“…Using these methods [Gauvrit et al 2014b], we can compute that, with a prior of 0.5, the probability that the string HHHHHTTTTT is random amounts to 0.58, whereas the probability that HTTHTHHHTT is random amounts to 0.83, thus confirming the common intuition that the latter is "more random" than the former.…”
Section: From Bias To Bayesmentioning
confidence: 53%
“…Humans too display biases in the same algorithmic direction, from their motion trajectories [Peng et al 2014] to their perception of reality [Chater 1999]. Indeed, we have shown that cognition, including visual perception and the generation of subjective randomness, shows a bias that can be accounted for with the seminal concept of algorithmic probability [Gauvrit et al 2014a, Gauvrit et al 2014b, Gauvrit et al 2014c, Kempe et al 2015, Mathy et al 2014]. Using a computer to look at human behavior in a novel fashion, specifically by using a reverse Turing test where what is assessed is the human mind and an "average" Turing machine or computer program implementing any possible compression algorithm, we will show that the human mind behaves more like a machine.…”
Section: The Turing Test Is Trivial Ergo the Mind Is Algorithmicmentioning
confidence: 88%
See 1 more Smart Citation
“…In our experiments we have used the acss R package [42] which implements the Coding Theorem Method [34,43] and the Block Decomposition Method [35].…”
Section: Resultsmentioning
confidence: 99%